Volatile anaesthetics enhance the metastasis related cellular signalling including CXCR2 of ovarian cancer cells - Iwasaki, Masae (Oncotarget, 2016)
The majority of ovarian cancer patients relapse after surgical resection. Evidence is accumulating regarding the role of surgery in disseminating cancer cells; in particular anaesthesia may have an impact on cancer re-occurrence. Here, we have investigated the metastatic potential of volatile anaesthetics isoflurane, sevoflurane and desflurane on ovarian cancer cells. Human ovarian carcinoma cells (SKOV3) were exposed to isoflurane (2%), sevoflurane (3.6%) or desflurane (10.3%) for 2 hours. Metastatic related gene expression profiles were measured using the Tumour Metastasis PCR Array and qRT-PCR. Subsequently vascular endothelial growth factor A (VEGF-A), matrix metalloproteinase 11 (MMP11), transforming growth factor beta-1 (TGF-β1) and chemokine (C-X-C motif) receptor 2 (CXCR2) proteins expression were determined using immunofluorescent staining. The migratory capacities of SK-OV3 cells were assessed with a scratch assay and the potential role of CXCR2 in mediating the effects of volatile anaesthetics on cancer cell biology were further investigated with CXCR2 knockdown by siRNA. All three volatile anaesthetics altered expression of 70 out of 81 metastasic related genes with significant increases in VEGF-A, MMP-11, CXCR2 and TGF-β genes and protein expression with a magnitude order of desflurane (greatest), sevoflurane and isoflurane. Scratch analysis revealed that exposure to these anesthetics increased migration, which was abolished by CXCR2 knockdown. Volatile anaesthetics at clinically relevant concentrations have strong effects on cancer cell biology which in turn could enhance ovarian cancer metastatic potential. This work raises the urgency for further in vivo studies and clinical trials before any conclusions can be made in term of the alteration of clinical practice.